Food intake and lifestyle practices of business process outsourcing (BPO) workers from Cainta, Rizal and Los Banos, Laguna - Barrion, Aimee Sheree A.; Villegas, Aileen Fay M.; Yee, Marites G. (2014)
The industry of business process outsourcing (BPO) has greatly contributed to the economic and communication status of the country. However, people working in BPO companies have been attributed to different nutrition and lifestyle problems. This study aimed to determine the association between the food intake and lifestyle practices of BPO workers. A total of 64 respondents were involved in the study; 47 were from Cainta, Rizal and 17 were from Los Banos, Laguna. Moderate associations between the food intake and lifestyle practices of the BPO workers particularly in terms of energy and smoking; protein and physical activity; and phosphorus and coffee consumption were observed. The average one-day food intake of the BPO workers was 756.0 g with the highest proportion from cereals and cereal products in terms of food groups followed by meat products and highest proportion from carbohydrates in terms of energy derived from macronutrients. The one-day meat pattern of the BPO workers with a total energy count of around 1464 kcal, consisted of cereal, meat and miscellaneous with rice as the most commonly consumed food item. Moreover, more than half of the study population was able to meet the recommended amounts of protein, niacin, phosphorus, and iron. The common reported lifestyle practices included coffee consumption, smoking, alcohol drinking, and engagement in physical activities.
Keywords: Business process outsourcing (BPO)